The Influence of Capital Expenditure Realization, Financing Expenditure and Regional Original Income on the Financial Performance of Regional Governments in West Nusa Tenggara Province - Robi Yahya; Ikhwan Wadi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the effect of capital expenditure realization, financing expenditure, and Locally-Generated Revenue (Pendapatan Asli Daerah/PAD) on the financial performance of local governments in West Nusa Tenggara Province. This research employs a quantitative approach using the Partial Least Square (PLS) method, processed based on secondary data derived from the financial reports of district/city governments in West Nusa Tenggara Province. The analysis results show that capital expenditure realization, financing expenditure, and Locally-Generated Revenue each have a positive and significant effect on local government financial performance. Optimal management of these three components has been proven to strengthen regional fiscal independence, improve the effectiveness and efficiency of budget management, and support sustainable regional development. These findings indicate that improving the quality of capital expenditure planning and realization, controlling financing expenditure, and optimizing the collection of Locally-Generated Revenue should be prioritized in the formulation of regional fiscal policy. This study is expected to serve as a reference and consideration for local governments in formulating better financial management policies to sustainably improve regional financial performance.